Recalcitrant Septic Nonunion of the Ulna - Bech, Niels (Cureus, 2020)
An infected diaphyseal forearm nonunion can be a challenge. After several failed salvage procedures, the patient can be left with residual pain, shortening, bone loss, and poor soft tissue envelope. Keystones for infected nonunion treatment are debridement, cultures, antibiotics, stability, and restore alignment. This report describes the current literature on the treatment of forearm nonunion, and we present a case of a recalcitrant infected ulna nonunion that ultimately healed after 12 surgeries.